Plasma-assisted “waste-to-energy” processes - Zhovtyansky, V.A.; Kolesnikova, E.P.; Iakymovych, M.V. (Вопросы атомной науки и техники, 2017)
The environmental safety and energy efficiency of the processes of alternative gaseous fuels production based on the conversion of biomass waste using plasma-steam technology are discussed. The plasma-steam installation for waste processing, that eliminates the risk of dioxins and furans production in the process of gasification is briefly described. The problems of minimization nitrogen oxides emission as well as exception into the environment of heavy metals are discussed. It is shown that the proposed variant of the processing technology correspond to the general idea of numerous publications in the world scientific literature, known as the Waste to Energy. Обсуждаются вопросы экологической безопасности и энергетической эффективности процессов производства альтернативного газового топлива на основе преобразования отходов биомассы с использованием пароплазменной технологии. Кратко описана пароплазменная установка для переработки отходов, исключающая риск образования диоксинов и фуранов в процессе газификации. Обсуждаются проблемы минимизации выбросов оксидов азота, а также исключения попадания в окружающую среду тяжёлых металлов. Показано, что предлагаемый вариант технологии переработки отходов соответствует общей идее многочисленных публикаций в мировой научной литературе, известной как «производство энергии из отходов». Обговорюються питання екологічної безпеки та енергетичної ефективності процесів виробництва альтернативного газового палива на основі перетворення відходів біомаси з використанням пароплазмової технології. Коротко описана пароплазмова установка для переробки відходів, що виключає ризик утворення діоксинів і фуранів у процесі газифікації. Обговорюються проблеми мінімізації викидів оксидів азоту, а також унеможливлення потрапляння в навколишнє середовище важких металів. Показано, що пропонований варіант технології переробки відходів відповідає загальній ідеї численних публікацій у світовій науковій літературі, відомій як «виробництво енергії з відходів».